Comparative biochemical features of wild-type and purple cashew (Anacardium occidentale L.) - Jyothi, N.V.; Ajith, Akhil; Ramesha, B.; Hebbar, K.B.; Ramesh, S.V. (Journal of Plantation Crops, 2024)
The comparative biochemical features of both the wild-type and purple-coloured cashew apple varieties are presented. The total soluble sugar content in purple cashew apples was higher (13.96%) than that in normal cashew apples (6.78%). Compared with purple cashews, wild-type cashew apples have a high titratable acidity (0.224%) as they contain more ascorbic acid (342.85 mg/100 g) than purple cashew apples (228.57 mg/100 g). The total polyphenol content of purple fruit leaves (8.04 mg GAE/g), peels (4.532 mg GAE/g), and pulp (2.067 mg GAE/g) was higher than that of wild-type cashews. Additionally, the flavonoid content (9.423 mg/g in leaves, 4.923 mg/g in apple peels, and 3.688 mg/g in cashew pulp) was higher in the purple cashew than in the wild-type cashews. Chlorophyll a, b, and total chlorophyll contents in wild-type cashew leaves (0.287 mg/g, 0.176 mg/g, and 0.463 mg/g, respectively) were greater than those in purple cashew leaves. However, the chlorophyll concentration in the fruit was found to be very minimal. Although the carotenoid content of the fruit was high in the wild-type cashew (22.83 g/100 g), the carotenoid concentration in the purple cashew leaves (83.475 g/100 g) was greater than that in the normal cashew leaves. Analysis of the anthocyanin contents suggested that the leaves and peels of plants with the purple genotype had relatively high anthocyanin contents (38.499 mg cyanidin-3-glucoside equivalents/kg (C3GE/kg) and 25.87 mg C3GE/kg) compared to those of plants with the wild-type cashews (0.157 and 0.951 mg C3GE/kg, respectively). These biochemical constituents of purple cashew suggest its potential application in the development of cashew apple-based nutritional products.